Universality of Management in dealing with the impacts of climate change in Asian countries - Tienne Nhung (Journal of Asian Multicultural Research for Economy and Management Study, 2023)
The management of the effects of climate change in Asian nations is the focus of this review of the literature. Asia is a region with great cultural, geographical, and socioeconomic variety. The review emphasizes the importance of management principles, which, despite their universal relevance, call for careful adaptation in order to successfully handle the many problems that climate change presents. Planning, organizing, leading, and controlling are among the management principles that are acknowledged as essential instruments for sound decision-making and strategy implementation. They act as an all-encompassing framework that cuts beyond divisions of labor and industry. While organization guarantees effective strategy execution, planning establishes precise climate-related objectives and distributes resources. Leadership encourages a culture of environmental responsibility and inspires support for climate measures among stakeholders. Finally, control entails monitoring development and making necessary strategy adjustments. However, understanding the regional and cultural differences among Asian nations is necessary for the effective application of management principles. It is essential to strike the correct balance between specialization and universality. Additionally crucial to adjusting to the ever-changing difficulties of climate change are inventiveness and flexibility. Futures in Asia that are climate resilient are built on the understanding that management concepts are universal and can be tailored to particular situations. The insights gleaned from this analysis are priceless in tackling the effects of climate change on a worldwide scale. In the diverse and dynamic landscape of Asian countries, they underscore the significance of management concepts in fostering sustainability, resilience, and environmental responsibility.